The role of servitization for small firms: drivers versus barriers. (2015) - Confente, Ilenia; Buratti, Andrea; Russo, Ivan
The purpose of this study was to explore the servitization approach in order to understand the development of this trend among small Italian companies. In doing so, this study adopted a qualitative method and data were collected via in-depth interviews with managers of firms belonging to the footwear industry - an important sector for the Italian economy. Data analysis was realised through NVivo software, thereby providing a first understanding of the drivers that lead these companies to become 'servitized', as well as the main obstacles they face when considering providing services beyond their core offering. This study suggests important implications both for managers and marketing scholars. For academics, it extends the existing knowledge of the factors that influence this organisational and managerial change, and enriches the body of knowledge of the main drivers of and barriers to servitization. For practitioners, it helps in the understanding of the main advantages and potential obstacles to developing a servitization process.